Selected basic documents related to the international criminal court - Internacional Criminal Court (: International Criminal Court Publication, 2011)
Contiene: Instrumensts. Rules and regulations. Resolutions. Other related documents
Incluye anexos
Keywords: CORTE INTERNACIONAL DE JUSTICIA; DERECHO; DERECHO PENAL